2018
DOI: 10.1002/rmb2.12256
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in adolescent and young adult cancer patients: From a part of a national survey on oncofertility in Japan

Abstract: PurposeThis study evaluated the current status of reproductive disorders and provision of information on oncofertility to female adolescent and young adult (AYA) cancer patients in Japan.MethodsA national survey of AYA cancer survivors was conducted. Children were <15 years old, and AYAs were 15‐39 years old. Results from the survivors of other than gynecological disease who underwent chemotherapy were analyzed.ResultsAmong the survivors, 41.4% were concerned about their reproductive function and infertility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Japan is also one of advanced country which has guideline of FP treatment collaborate JSFP with JSCO (Japan Society of Clinical Oncology) (24). JSFP may start a registration system for FP treatment within 1 year to understand the present status of FP in Japan based on national survey for FP (25, 26). However, FP for C-A patients is not as common as FP for adult cancer patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…Japan is also one of advanced country which has guideline of FP treatment collaborate JSFP with JSCO (Japan Society of Clinical Oncology) (24). JSFP may start a registration system for FP treatment within 1 year to understand the present status of FP in Japan based on national survey for FP (25, 26). However, FP for C-A patients is not as common as FP for adult cancer patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with a recent survey of 167 female adolescents and young adults from Japan that demonstrated that only 48% of patients with nonbreast and nonhematologic malignancies had received information about the association of cancer therapy with reproductive organ health. 13 This finding suggests that there exists a need both in the US and elsewhere to identify strategies to increase fertility education and indicated referrals to fertility specialists for adult patients with newly diagnosed cancers.…”
Section: Discussionmentioning
confidence: 99%
“…With the dramatic developments in cancer treatments, “cancer survivorship” is regarded as an important issue in cancer therapy. “Fertility” has been a particular concern among cancer survivors and medical practitioners . Furthermore, facilitation of pregnancy and delivery after cancer treatment is one solution to recovering the reduced birthrate of leading countries that have a low total fertility rate.…”
Section: Introductionmentioning
confidence: 99%